2020
DOI: 10.1007/s00068-020-01486-y
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of fracturoscopy on the incidence of surgical site infections post tibial plateau fracture surgery

Abstract: Purpose Surgical treatment of tibial plateau fracture (TPF) is common. Surgical site infections (SSI) are among the most serious complications of TPF. This multicentre study aimed to evaluate the effect of fracturoscopy on the incidence of surgical site infections in patients with TPF. Methods We performed a retrospective multicentre study. All patients with an AO/OTA 41 B and C TPF from January 2005 to December 2014 were included. Patients were divided into three groups: those who underwent arthroscopic red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
(23 reference statements)
0
5
0
1
Order By: Relevance
“…Clinical resolution of infection occurred after an average of 3.3 additional procedures (55). In 2000 patients treated with ORIF by henkelman et al in 2020, the rate of surgical site infection was 4.7% (93/2000) (56). In 2022, the rate of deep infection in OTA/AO type C tibial plateau reported by Bullock et al was 6% (57).…”
Section: Infectionmentioning
confidence: 98%
“…Clinical resolution of infection occurred after an average of 3.3 additional procedures (55). In 2000 patients treated with ORIF by henkelman et al in 2020, the rate of surgical site infection was 4.7% (93/2000) (56). In 2022, the rate of deep infection in OTA/AO type C tibial plateau reported by Bullock et al was 6% (57).…”
Section: Infectionmentioning
confidence: 98%
“…Compared with open reduction internal fixation, the ARIF technique has been proven to lead to faster postoperative recovery and better clinical outcomes in the treatment of tibial fractures [ 24 ]. Moreover, the severe knee injuries are at higher risk of infection, and the ARIF technique can reduce the rates of surgical site infections [ 25 ]. Therefore, we finally chose ARIF technique to treat anteromedial tibial plateau fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars pointed out that 60 patients with tibial plateau fractures suffered from low energy injury and were treated by internal plate fixation [ 22 ]. The patients were followed up for one year, and the results showed that the excellent and good rate of knee joint function recovery was only 85% and 15% of the patients had knee traumatic arthritis [ 23 ]. When observing the X-ray films of the patients' knee joints, it was found that different degrees of degeneration could be observed in the patients' knee joints, accounting for 30%.…”
Section: Discussionmentioning
confidence: 99%